2007
DOI: 10.1093/protein/gzm020
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of a recombinant antibody fragment with a homo-amino-acid polymer: effects on biophysical properties and prolonged plasma half-life

Abstract: Chemical conjugation of small recombinant proteins with polyethylene glycol (PEG) is an established strategy to extend their typically short circulation times to a therapeutically useful range. We have investigated the production of a genetic fusion with a glycine-rich homo-amino-acid polymer (HAP) as an alternative way to attach a solvated random chain with large hydrodynamic volume. The anti-HER2 Fab fragment 4D5 was used as a model system and fused with either 100 or 200 residue polymers of the repetitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 58 publications
(82 reference statements)
4
65
0
Order By: Relevance
“…Furthermore, binding of scDb and scDb-ABD to these cell lines was not affected in the presence of serum albumin. This finding is in accordance with results obtained for a half-life-extended anti-HER2 Fab 4D5, which was either fused to the same ABD or an albumin-binding peptide (AB.Fab4D5) (12,13). In contrast, different results were described for PEGylated antibody fragments.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, binding of scDb and scDb-ABD to these cell lines was not affected in the presence of serum albumin. This finding is in accordance with results obtained for a half-life-extended anti-HER2 Fab 4D5, which was either fused to the same ABD or an albumin-binding peptide (AB.Fab4D5) (12,13). In contrast, different results were described for PEGylated antibody fragments.…”
Section: Discussionsupporting
confidence: 90%
“…The synthetic genes for most PAS sequences used in this study were either obtained by ligation of short hybridized oligodeoxynucleotide pairs encoding repetitive amino acid sequence units according to a previously described strategy18 or as assembled longer synthetic DNA fragments with minimized repeat on the nucleotide sequence level 8. The PAS polypeptides were produced in the cytoplasm of E. coli KS272 as C‐terminal fusion proteins with E. coli thioredoxin (TrxA; UniProt ID: P0AA25).…”
Section: Methodsmentioning
confidence: 99%
“…They also showed that the protein tags with the most disorder can be used not only for the increase in the solubility of target proteins as the aforementioned entropic bristles do, but also can serve as important tools for extending half-life of proteins and for characterizing their biological properties, e.g., binding. 129 An incomplete list of the disordered serine-containing tags shown to increase the half-life of a protein of interest inside the cell includes an unstructured recombinant polypeptide of 864 amino acids with the PESTAG composition, called XTEN, 130,131 serine-glycine-containing HAP 132 and proline-alanine-serine-containing PAS tags, 133 as well as tags containing PESAK, PASTDH, and PASTD repeats. 134,135 Some functions of serine-rich proteins To get a clue on what proteins with high serine content can be used for biologically, functions of several proteins with polyserine regions are outlined below.…”
Section: Serine and Functions Of Idps/idprsmentioning
confidence: 99%